2012
DOI: 10.5021/ad.2012.24.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Pruritus on the Quality of Life: A Preliminary Study

Abstract: BackgroundPruritus affects the quality of life (QoL) in the patients. However, little is known of the impacts of itching on the QoL in the literature.ObjectiveIn this study, a questionnaire eliciting specific responses about pruritus was used to determine the effect of itching and its severity on QoL in chronic pruritic patients.MethodsOne hundred ten adult patients with chronic pruritus were surveyed. Once itch severity had been self-reported by patients, together with Skindex-29, they have been given the 18-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 25 publications
6
54
0
Order By: Relevance
“…The distribution domain including 15 body part item. Scoring system :( 0-5) indicates no pruritus, (6)(7)(8)(9)(10)(11)(12)(13)(14) indicates mild pruritus, (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) indicates moderate pruritus and (25-35) indicates severe pruritus.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution domain including 15 body part item. Scoring system :( 0-5) indicates no pruritus, (6)(7)(8)(9)(10)(11)(12)(13)(14) indicates mild pruritus, (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) indicates moderate pruritus and (25-35) indicates severe pruritus.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…The preparation of peppermint oil and sunflower oil done by faculty staff member specialized in herbal medicine department from faculty of Pharmacy Cairo University. Aromatherapy consists of mix between two oils includes peppermint oil and sunflower oil [19]. The total amount after preparation stored in 50 ml plastic clean container .…”
Section: Procedures For Data Collectionmentioning
confidence: 99%
“…3,4 Previous studies found that itch causes just as much quality-of-life disturbance as does pain. 5 Chronic pruritus negatively effects all patients' activities of daily living and their emotional well-being.…”
Section: Lack Of Appreciation Of the Patient-burden Of Pruritusmentioning
confidence: 99%
“…5 Chronic pruritus negatively effects all patients' activities of daily living and their emotional well-being. 3,4 Despite itch being a commonly reported symptom, 6 it is not routinely assessed by most clinicians. Patients often think that health professionals do not take their itch seriously, 7 which may result in inadequate treatment and poor patient satisfaction.…”
Section: Lack Of Appreciation Of the Patient-burden Of Pruritusmentioning
confidence: 99%
“…Multiple PRO instruments were shown to be good assessments of itch, including the Dermatology Life Quality Index, 2 ItchyQOL, 3 and Skindex. 4 Each has strengths and weaknesses, and the decision about which to use can be based on personal preference by the clinician. These can be completed in the waiting or examination room before seeing the clinician.…”
Section: To the Editormentioning
confidence: 99%